Identification of Microplastic Polymers in Packaged Sugar-Sweetened Beverages and Associations with Children’s Diabetes Mellitus Risk - Aprilianti, Rafika; Shofiyah, Rohimatush; Khomsah, Khusnatul (Environmental Pollution Journal, 2025)
Microplastics are known to be composed of many chemical compounds, and there are compounds that act as hormone disruptors that can trigger insulin resistance. Children are the highest consumers of sugar-sweetened beverages in packaging (SSBs), which generally have plastic packaging. The study aimed to identify the presence of microplastics and polymer types of SSBs that are widely consumed in Indonesia, and evaluate their potential impact on health, especially the risk of diabetes mellitus in children. SSBs samples were taken from several brands in traditional and modern stores in Gresik Regency. The analysis was conducted by FT-IR test with the control variable being the water source from Beji Spring, Wonosalam. Furthermore, a literature review was conducted on the relationship between microplastics and diabetes mellitus in children. The results showed that the microplastics detected were filaments and fibers with polymers PET, PP, POM, EVOH and others. Microplastics are known to affect the performance of the pancreas so that it will cause diabetes mellitus in children. Reflecting on this condition, the government is expected to make quality standards for microplastics because of their harmful impact on the human body, especially children.